The impact of perceived value and affection on Chinese residents' continuous use intention of mobile health science information: An empirical study - Tian, Kun; Hao, Lijie; Xuan, Wenxia; Phongsatha, Thanawan; Hao, Ruimin; Wei, Wenjing (Frontiers in Public Health, 2023)
The Chinese government has paid constant attention to improving Chinese residents’ health literacy by disseminating health science information through the internet. This has become an essential means to improve Chinese residents’ health literacy. Therefore, exploring Chinese residents’ perceived value and emotional response to mobile health science information is significant for determining Chinese residents’ satisfaction and use intention. This study employed the cognition-affect-conation model to evaluate perceived value, arousal, pleasure, trust, satisfaction, and continuous use intention. A mobile device was used to obtain health science information of 236 Chinese residents through an online survey. The results showed that Chinese residents’ perceived value of health science information obtained from mobile devices directly affected their degree of arousal, pleasure, and trust. Their degree of arousal, pleasure, and trust directly affected satisfaction, which subsequently affected continuous use intention. Simultaneously, trust directly affected continuous use intention. Degree of arousal had a direct impact on degree of pleasure, and pleasure also imposed a direct effect on trust. The results of this study is an academic and practical reference for improving mobile health science popularization information.